2017
DOI: 10.1039/c7sc03974c
|View full text |Cite
|
Sign up to set email alerts
|

Fluoro-substituted cyanine for reliablein vivolabelling of amyloid-β oligomers and neuroprotection against amyloid-β induced toxicity

Abstract: A fluoro-substituted cyanine showing reliable in vivo labelling of Aβ oligomers and potent neuroprotective effect against Aβ-induced toxicities is reported as a novel theranostic agent for the early diagnosis and therapy of Alzheimer's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
96
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(97 citation statements)
references
References 28 publications
(29 reference statements)
1
96
0
Order By: Relevance
“…The selectivity of other oligomer-specific dyes has been rationalized through docking studies with the X-ray crystallographic structures of triangular trimers reported by our laboratory. 2224 BODIPY-based probes, 22 developed by the Chang group, spiropyran-based probes, 23 developed by the Yi group, and cyanine-based probes, 24 developed by the Wong group, all specifically stain Aβ oligomers. To explain the oligomer-specific reactivity of these probes, all three groups performed docking simulations, in which the probes were docked on a triangular trimer formed by an Aβ-derived peptide (PDB 4NTR).…”
Section: Resultsmentioning
confidence: 99%
“…The selectivity of other oligomer-specific dyes has been rationalized through docking studies with the X-ray crystallographic structures of triangular trimers reported by our laboratory. 2224 BODIPY-based probes, 22 developed by the Chang group, spiropyran-based probes, 23 developed by the Yi group, and cyanine-based probes, 24 developed by the Wong group, all specifically stain Aβ oligomers. To explain the oligomer-specific reactivity of these probes, all three groups performed docking simulations, in which the probes were docked on a triangular trimer formed by an Aβ-derived peptide (PDB 4NTR).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that inorganic filler such as rattan powder, glass fiber, etc. increases the tensile modulus of polymeric composites, yet causing the decrease of the strength and toughness . This could be attributed to the stress concentration or poor fiber‐matrix adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…As part of our effort on developing versatile probes for Aβ species imaging in vivo, we report herein a novel nontoxic and blood brain barrier (BBB) permeable NIR/MR dual‐modal imaging probe based on Aβ‐targeting carbazole‐based cyanine NIR fluorophores chemically conjugated onto superparamagnetic iron oxide nanoparticles (Fe 3 O 4 NPs) affording NIR/MR active Fe 3 O 4 @SiO 2 @SLCONHR NPs. Strong binding interactions between Aβ species and cyanine fluorophore have given rise to a large fluorescence enhancement in NIR region and MR signal.…”
Section: Methodsmentioning
confidence: 99%